2013
DOI: 10.1016/j.nantod.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution, serial intravital microscopic imaging of nanoparticle delivery and targeting in a small animal tumor model

Abstract: Nanoparticles are under active investigation for the detection and treatment of cancer. Yet our understanding of nanoparticle delivery to tumors is limited by our ability to observe the uptake process on its own scale in living subjects. We chose to study single-walled carbon nanotubes (SWNTs) because they exhibit among the highest levels of tumor uptake across the wide variety of available nanoparticles. We target them using RGD (arginine-glycine-aspartic acid) peptide which directs them to integrins overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 46 publications
(50 reference statements)
2
62
0
Order By: Relevance
“…Perhaps unsurprisingly, the targeted NP exhibited greater tumor accumulation at early time points within six hours of administration, while passive tumor penetration and EPR effects dominated accumulation at later time points. Unexpectedly however, NP targeting again led to enhanced tumor retention at very late time points (>1 week post-administration), while non-targeted NPs were no longer detectable [72]. These results are somewhat consistent with another study that found RGD-liposomes could transiently saturate binding sites on vasculature.…”
Section: Discovering Np Action By High Resolution Ivm Imagingsupporting
confidence: 83%
“…Perhaps unsurprisingly, the targeted NP exhibited greater tumor accumulation at early time points within six hours of administration, while passive tumor penetration and EPR effects dominated accumulation at later time points. Unexpectedly however, NP targeting again led to enhanced tumor retention at very late time points (>1 week post-administration), while non-targeted NPs were no longer detectable [72]. These results are somewhat consistent with another study that found RGD-liposomes could transiently saturate binding sites on vasculature.…”
Section: Discovering Np Action By High Resolution Ivm Imagingsupporting
confidence: 83%
“…Intratumoral extravasation and extravascular transport dynamics of c 60 -serPF While NP vascular delivery, extravasation and changes in intravascular and extravascular NP concentration have been quantified over various time scales from minutes 31,34,39 to days 35 using time lapse imaging, this article presents time lapse imaging with continuous quantification of NP extravasation on a second-to-second timescale in select and global ROIs, representing water-soluble fullerene derivative biotransport dynamics. At the tumor periphery, where IVM imaging has captured these transport dynamics, convective forces play a role in microvascular delivery, 32 while both convection and diffusion contribute to extravascular transport.…”
Section: 25mentioning
confidence: 99%
“…Furthermore, while many IVM studies quantitatively monitor drug or NP kinetics with temporal resolution on the order of minutes to hours [34][35][36][37] and even days, 35 no study has quantitatively tracked initial NP or drug delivery influx dynamics in the tumor microenvironment at a resolution on the timescale of seconds. As C 60 -serPF clears rapidly from the blood stream (as evidenced by the color change of mouse urine occurring within 15 min of C 60 -serPF injection 21 ), capture of C 60 -serPF …”
Section: Introductionmentioning
confidence: 99%
“…5) [28]. Other research efforts have exploited IVM imaging to examine the effectiveness of arginine-glycine-aspartic acid (RGD) peptide conjugated to quantum dots [77], carbon single-wall nano-tubes [78], and liposomal nanoparticles [79]. …”
Section: Visualize and Evaluate Vascular Transportmentioning
confidence: 99%